INCREASING THE EFFICIENCY OF INVESTMENT ACTIVITY IN SMALL BUSINESS AND PRIVATE ENTREPRENEURS (Conference Zone, 2022)
This article describes the role and importance of small business and entrepreneurship in the socio-economic development of the country. At the same time, issues such as increasing the efficiency of investment activities in small business and private entrepreneurship were widely covered.